GAMBARAN MUAL-MUNTAH, GANGGUAN PENGECAPAN, DAN PEMILIHAN MAKANAN SPESIFIK PADA KEHAMILAN - Dita Marisca; Ardesy Melizah Kurniati; Wardiansyah Wardiansyah; Syifa Syifa (Alami Journal (Alauddin Islamic Medical) Journal, 2022)
Pregnant women are one of the groups that are vulnerable to nutritional problems. Hormonal changes in pregnant women are suspected to be the cause of changes in the eating habits of pregnant women and if not addressed, will affect their nutritional status. This study aimed to determine the problems affecting pregnant women's food intake, including emesis during pregnancy, taste disorders, and the selection of specific foods in pregnant women. This study is a descriptive study with a cross-sectional approach. Samples were taken using a consecutive sampling method, with criteria for pregnant women in the first trimester at Al-Syifa Clinic Palembang who were willing to participate. We took primary data were taken through questionnaires and interviews with 48 respondents. This study showed that 43 people (89.6%) of respondents had a history of emesis during pregnancy. Twenty-eight people (58.3%) had a moderate degree of hyperemesis gravidarum, and only one had a severe degree of hyperemesis gravidarum (2.1%). A total of 47 people (97.7%) admitted to having taste disorders. Pregnant women in this study tended to experience a decrease in sweet, salty, bitter, and sour tastes. Thirty-three pregnant women (68.8%) wanted specific foods, and 44 (91.7%) avoided certain foods. Further research is needed to identify the relationship between hyperemesis gravidarum, taste disorders, and specific food choices in pregnant women on their diet and nutritional status.